2021
DOI: 10.1101/2021.05.25.21257505
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plitidepsin has a positive therapeutic index in adult patients with COVID-19 requiring hospitalization

Abstract: Plitidepsin is a marine-derived cyclic-peptide that inhibits SARS-CoV-2 replication at low nanomolar concentrations by the targeting of host protein eEF1A (eukaryotic translation-elongation-factor-1A). We evaluated a model of intervention with plitidepsin in hospitalized COVID-19 adult patients where three doses were assessed (1.5, 2 and 2.5 mg/day for 3 days, as a 90-minute intravenous infusion) in 45 patients (15 per dose-cohort). Treatment was well tolerated, with only two Grade 3 treatment-related adverse … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The drug was shown to inhibit viral replication, including in mice infected with SARS-CoV-2. It should be noted that the antiviral activity of the drug against SARS-CoV-2 is 27.5 times more potent than that of Remdesivir [103,104], and relevant clinical findings suggest potential effectiveness [105]. The drug is currently undergoing clinical evaluation (phase 3) in combination with Dexamethasone in approximately 610 patients (ClinicalTrials.gov, NCT04784559).…”
Section: Plitidepsinmentioning
confidence: 99%
“…The drug was shown to inhibit viral replication, including in mice infected with SARS-CoV-2. It should be noted that the antiviral activity of the drug against SARS-CoV-2 is 27.5 times more potent than that of Remdesivir [103,104], and relevant clinical findings suggest potential effectiveness [105]. The drug is currently undergoing clinical evaluation (phase 3) in combination with Dexamethasone in approximately 610 patients (ClinicalTrials.gov, NCT04784559).…”
Section: Plitidepsinmentioning
confidence: 99%
“…Plitidepsin has shown very potent antiviral activity in vitro and is currently under Phase 3 clinical assays. Preliminary results have shown that it is safe and positively influences the outcome of patients hospitalized with COVID-19 [53].…”
Section: Plitidepsinmentioning
confidence: 99%
“…This functional activity against SARS-CoV-2 has been demonstrated in mouse models with a potent antiviral activity with limited toxicity (90% inhibitory concentration = 0.88 nM) ( White et al, 2021 ). Given the promising results obtained at the preclinical level, Dr. Fernandez Sousa-Faro and his team at Pharma Mar started a phase I/II dose-escalating clinical trial, which proved the efficiency of the treatment, especially in patients with moderate infection ( Varona et al, 2021 , 2022 ). Given these results, PharmaMar recently obtained authorization to start a phase III clinical trial (NEPTUNO) to determine the efficacy of plitidepsin for the treatment of hospitalized patients with moderate COVID-19 infection.…”
Section: Covid-19 Vaccines (1)mentioning
confidence: 99%